Penggunaan Bahasa pada Perkembangan Industri Pariwisata di Surabaya: Studi Kasus Objek Wisata Museum Sepuluh Nopember - Sa'diyah, Ilmatus; Ariffa, Anggelia Hayuning; Agustina, Endang; Maghfiroh, Marjiatul; Kusnarto, Kusnarto (Universitas Ahmad Dahlan, 2023)
The tourism industry in Surabaya has had to adapt to the changing times marked by the entry of foreign languages into Indonesia. The phenomenon of the use of foreign languages in public spaces is often a problem. For that reason, this article was written based on research conducted to analyze the use of language and writing skills in Indonesian and foreign languages in one of the branches of tourism in Surabaya, namely Museum Sepuluh Nopember. This research is qualitative descriptive in nature using primary data from direct data sources, namely the utilization of indonesian in the tourism industry of Museum Sepuluh Nopember Surabaya. Data collection is done by documentation and observation method. In addition, the analytical method used is descriptive qualitative. Based on the analysis that has been done, the use of Indonesian in the Museum Sepuluh Nopember Surabaya tourism industry is not optimal. There are still several formats for the using and spelling of Indonesian and foreign languages that need to be corrected according to regulations of language institutions and the law on language use.